Evaluating the Efficacy and Safety of Hepatitis E Vaccination in Reproductive-Age Women: A Systematic Review and Meta-Analysis - Vaidas Jotautis; Antigoni Sarantaki (Vaccines)
Background: Hepatitis E virus (HEV) infection presents a significant health risk in endemic regions, especially for pregnant women, who face higher risks of severe complications, including maternal and fetal mortality. The recombinant HEV vaccine, HEV239, has demonstrated high efficacy in the general population, yet data on its safety and efficacy in women of a childbearing age remain limited. This systematic review and meta-analysis aim to evaluate the safety and effectiveness of HEV239 in this specific population, with a focus on pregnancy-related outcomes. Methods: A comprehensive search was conducted in PubMed, Embase, Cochrane Library, and Scopus, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were included if they reported outcomes on HEV239′s safety or efficacy in women of childbearing age, with data being extracted and analyzed for immunogenicity, HEV incidence, and maternal adverse events. The risk of bias was assessed using the Cochrane and Newcastle Ottawa Scales, and a random-effects meta-analysis was performed. Results: Three studies, enrolling over 23,000 participants, were included in the current systematic review, with two meeting the criteria for meta-analysis. HEV239 demonstrated high efficacy in preventing hepatitis E infection, with no significant increase in adverse pregnancy outcomes such as stillbirth or elective termination. However, there was an elevated risk of miscarriage (odds ratio [OR], 1.60; 95% confidence interval [CI], 0.99–2.57). The analysis revealed high heterogeneity for miscarriage outcomes (I2 = 67%), reflecting variability in study designs and populations. Conclusions: HEV239 is effective in preventing HEV infection among women of childbearing age, although caution is advised when administering the vaccine near conception due to potential miscarriage risks. Future studies should focus on understanding the biological mechanisms and timing-specific safety to guide vaccination recommendations.